2020
DOI: 10.1038/s41598-020-58396-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal periodontal status and ultrasonographic measurement of fetal growth: A longitudinal study

Abstract: the aim of this prospective cohort study was to investigate the association between intrauterine fetal growth patterns and periodontal status in pregnant women. fifty-three pregnant women were recruited. periodontitis was diagnosed based on probing pocket depth and clinical attachment level. Maternal urinary 8-hydroxy-2'-deoxyguanosine levels and body mass index were recorded. Ultrasonographic measurements of the biparietal diameter (BpD), abdominal circumference (Ac), and femur length (fL) were recorded, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Growing evidence supports a relationship between PD and female infertility related conditions, namely polycystic ovary syndrome (PCOS) [ 22 , 23 , 25 , 26 , 27 , 28 , 47 , 48 , 49 , 50 , 51 ], endometriosis [ 29 , 30 ] and obesity [ 52 , 53 , 54 , 55 , 56 ]. Furthermore, recent studies have substantiated the relationship between maternal PD as a potential risk factor of adverse pregnancy outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Periodontal therapy may prevent or reduce perinatal and maternal morbidity and mortality, especially in mothers at high risk [ 65 , 66 ], though a Cochrane review reported unclear evidence that periodontal treatment during pregnancy has an impact on preterm birth [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports a relationship between PD and female infertility related conditions, namely polycystic ovary syndrome (PCOS) [ 22 , 23 , 25 , 26 , 27 , 28 , 47 , 48 , 49 , 50 , 51 ], endometriosis [ 29 , 30 ] and obesity [ 52 , 53 , 54 , 55 , 56 ]. Furthermore, recent studies have substantiated the relationship between maternal PD as a potential risk factor of adverse pregnancy outcomes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Periodontal therapy may prevent or reduce perinatal and maternal morbidity and mortality, especially in mothers at high risk [ 65 , 66 ], though a Cochrane review reported unclear evidence that periodontal treatment during pregnancy has an impact on preterm birth [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also a place of communication between the fetus and the mother. We previously reported that the estimated fetal growth was suppressed in pregnant women with periodontal disease in late pregnancy compared with healthy controls [ 37 ]. As placental nutrient transport is associated with placental weight [ 38 ], maternal-gut-microbiota-derived substances may have reached the fetus via the placenta and triggered inflammatory gene expression on the fetal side.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations are necessary with a detailed classification of periodontitis, based on severity, complexity, extent, and distribution, in order to evaluate the actual impact of the periodontal condition on pregnancy. Until then, dental screening and treatment before conception is a reasonable recommendation to prevent oral problems during pregnancy 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Taniguchi-Tabata et al 14 investigated the association between intrauterine fetal growth patterns and periodontal status in 53 pregnant women, whose periodontitis was diagnosed based on Probing depth (PD) and CAL. The levels of maternal urinary 8-hydroxy-2'deoxyguanosine and the body mass index were recorded.…”
Section: Introductionmentioning
confidence: 99%